Environmental context, managerial cognition, and strategic action: an integrated view - Nadkarni, Sucheta; Barr, Pamela S. (Strategic Management Journal, 2008)
Abstract This study addresses an apparent disconnect between two views of strategic action: the ‘economic view,’ which contends that industry structure is the primary influence on strategic action, and the ‘cognitive view,’ which suggests that managerial cognition drives strategic action. We argue that this disconnect has created artificial boundaries between the two perspectives and has limited our ability to develop holistic explanations of strategic action. In response, we develop an integrated model that answers two questions: 1) Does industry context affect managerial cognition? 2) Does managerial cognition mediate the relationship between industry context and strategic responses to environmental changes? To examine these questions, we study the relationship between industry velocity, the structure of top management's cognitive representation of the environment, and the speed of response to environmental events. We find that industry velocity influences the structure of cognitive representations, which in turn influence the speed of response to environmental events. These results support our contention that both industry and cognition variables are critical in developing explanations of strategic actions. These results have implications for our understanding of the development of top managers' beliefs, the relationship between beliefs and action, and the nature of the complex relationship between industry context, managerial cognition, and strategic action. Copyright © 2008 John Wiley & Sons, Ltd.